1995
DOI: 10.1021/ac00107a008
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Nonionic Polyethoxylate Surfactants in Environmental Waters by Liquid Chromatography/Electrospray Mass Spectrometry

Abstract: A very sensitive and specific analytical procedure for determining nonionic polyethoxylate surfactants, such as aliphatic ethoxylate alcohols (AEOs) and nonylphenol polyethoxylates (NPEOs), in aqueous environmental samples using electrospray liquid chromatography/mass spectrometry is presented, This procedure involves passing 10, 100, 1000, and 4000 mt of raw sewage, treated sewage, river water, and drinking water samples,respectively, through a 1-g graphitized carbon black (GCB) extraction cartridge, By explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
160
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(165 citation statements)
references
References 16 publications
4
160
1
Order By: Relevance
“…In comparison to LLE technique, the solid phase extraction allows for reduction of analytes isolation time and consumption of solvents [16]. Moreover, the sample preparation step can be automated with use of SPE [17]. Several types of sorbents (graphitized black carbon, octadecylsilica or polymeric) were employed for the extraction of non-ionic compounds from environmental samples.…”
Section: Liquid Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to LLE technique, the solid phase extraction allows for reduction of analytes isolation time and consumption of solvents [16]. Moreover, the sample preparation step can be automated with use of SPE [17]. Several types of sorbents (graphitized black carbon, octadecylsilica or polymeric) were employed for the extraction of non-ionic compounds from environmental samples.…”
Section: Liquid Samplesmentioning
confidence: 99%
“…The MS-MS detector can be used to identification of non-ionics analytes (due to their mass spectra contain characteristic fragments that constitute additional confirmation) and usually provides higher selectivity at quantitative determination step [64]. For ionization of non-ionic analytes were applied two techniques: atmospheric pressure chemical ionization (APCI) [26] and electrospray ionization ESI (has demonstrated higher sensitivity) [17,63]. The identification and quantitative analysis of non-ionic SAA was performed with the ion trap mass, quadrupole and triple-quadrupole mass spectrometers [64][65][66][67].…”
Section: Final Determination Stepmentioning
confidence: 99%
“…Liquid-liquid extraction is the classical approach for surfactants extraction from water samples; however, because of its disadvantages, it has been widely replaced with solid-phase extraction (SPE). 14 Several works reported the use of solid-phase micro extraction and SPE with different sorbents such as alkylbonded silica, 15 graphitized carbon black (GCB) 16 and styrene-divinylbenzene resins. 17 Recent studies on the use of surfactant-coated mineral oxides columns for SPE have demonstrated that these new sorbent materials are promising tools for the extraction/preconcentration of organic compounds in a wide polarity range.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid-liquid extraction [2], sublation [3] and mainly solid-phase extraction (SPE) were used to recover AAEs from aqueous matrices. SPE exploited the hydrophobicity of the AAE molecule and employed sorbents were alkyl-bonded silica [4][5][6] and graphitized carbon black [7,8]. Extraction of AAEs from the solid phase was carried out using traditional Soxhlet liquidsolid extractor [3].…”
Section: Introductionmentioning
confidence: 99%
“…Liquid chromatography (LC) seemed to be the most suitable separation technique. But, the resolution power of a single liquid chromatographic method being insufficient, the complete analysis of AAEs required either coupling of liquid chromatography with an identification detection mode as mass spectrometry (MS) [4,5,7,[14][15][16][17] or combination of two complementary liquid chromatographic methods [2,[18][19][20][21]. This paper compares different analytical procedures to measure AAEs in wastewater.…”
Section: Introductionmentioning
confidence: 99%